A hundred key questions for the post-2015 development agenda - United Nations Research Institute for Social Development (UNRISD) (United Nations Research Institute for Social Development (UNRISD), 2015)
With a new development framework under way and an increasingly urgent need to address political, socioeconomic and environmental issues on a global scale, this is a critical moment for the international development agenda. Almost 15 years after the Millennium Declaration, a new phase for international development is about to begin and, with it, comes the opportunity to critically assess how new development goals and milestones are likely to be shaped and delivered. This paper assumes that a greater understanding of development needs and practices can better sustain a new agenda for change, and that a key step in this process is to identify priorities based on both new and long-standing knowledge gaps, to help orient decision-making processes and funding allocation in academia and beyond. This paper present the results of a consultative and participatory exercise that addresses the need to articulate and better align the research interests and priorities of academics and practitioners working on international development in a post-2015 international development framework. The exercise was organized around a two-stage consultation and shortlisting process. A four-months open consultation was conducted, offering development stakeholders and individuals the opportunity to submit their questions. People were invited to submit questions related to some of the thematic priorities that guided the "World We Want" campaign-a global stakeholder consultation conducted by the UN between 2010 and 2014 involving governments, civil society and lay citizens. In this first phase, A total of 705 individuals from 109 organizations based in 34 countries were involved in the formulation of 704 questions. The questions were then discussed and shortlisted during a two-day workshop with academic and practitioners representing different world regions and areas of expertise, among whom are also the authors of this paper. After the final shortlisting, questions were regrouped into nine macro-thematic sections: governance, participation and rights; environmental sustainability; food security, land and agriculture; energy and natural resources; conflict, population dynamics and urbanization; economic growth, employment and the private sector; social and economic inequalities; health and education; development policies, practices and institutions. The final 100 questions address a varied combination of long-standing problems that have hindered the development agenda for decades as well as new challenges emerging from broader socioeconomic, political and environmental changes. Well-established concerns about the rights of women, and of vulnerable groups such as poor workers, small-scale farmers, people with disabilities, children and ethnic minorities feature alongside emerging issues, including the role of business in protecting human rights, and information and communication technologies as tools for empowerment and social integration. Similarly, traditional concerns linked to rural livelihoods, land tenure and agricultural production are presented together with environmental sustainability, natural resource extraction, urbanization, food security, and climate change adaptation and mitigation. While civil society and the empowerment of marginalized populations are recognized as key for development, questions on new actors including the private sector, emerging economic powers and new middle-income countries as development donors and partners feature heavily in the shortlist. The questions also reflect the mainstreaming of gender perspectives into a wide range of development areas, helping to cement the view that gender should be considered central to future development initiatives. A large number of the submitted questions (102) specifically addressed broader issues related to development politics, practices and institutions. This outcome, combined with the fact that a number of these were included in the final shortlist, highlights the fact that there is a critical need for a deeper collective reflection on the role and relationships of different actors in international development, and the impact that contemporary economic and political scenarios will have on the development agenda. We envision our list of 100 questions contributing to inform the post-2015 agenda and future development-related research priorities of international, governmental and non-governmental organizations. But, perhaps more centrally, we believe that these questions can act as starting points for debate, research and collaboration between academics, practitioners and policy makers. The value of research exercises such as this one rely on the ability of a variety of stakeholders to reach consensus around a set of research priorities put forward by anyone willing to engage in the process. We believe that the process of co-production we set out here, of debate and discussion between different stakeholders, is essential for successfully and effectively tackling the key challenges ahead for the international development agenda.
Keywords: 330